(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
An individual of the Catius Rona Hedge Blue Udara rona catius (Fruhstorfer, 1910) was found and photographed on 28 April 2018 in Jambul Highlands, South Sumatra province, Indonesia. After photographed, the butterfly was identified using major references. This incidental finding of Udara rona catius is a first record for southern Sumatra. The potential host plants of U. rona catius in Jambul Highlands are plants from family Euphorbiaceae (Aporosa sp., Cleoxylon sp., Croton sp., Endospermum sp., Macaranga sp. and Phyllanthus sp.) and Fagaceae (Castanopsis sp., Lithocarpus sp. and Quercus subsericea). Â Â Â Â Â Â